Cancer-related cryptogenic stroke involving the bilateral anterior and the posterior circulations: Diagnostic value of clinical and imaging characteristics - Xu, Yifan; Wu, Zhuang; Xu, Hang (Frontiers in Neurology, 2022)
Objectives: This study analyzed the clinical and imaging characteristics of the patients with cancer-related cryptogenic stroke (CCS) involving the bilateral anterior and the posterior circulation (three circulation) and evaluate the diagnostic value of clinical and imaging features for patients with cryptogenic stroke involving three circulation (CST). Methods: Of the 12580 patients with acute ischemic stroke, 148 patients with CST from May 2017 to November 2021 were divided into the cancer group (n = 81) and the non-cancer group (n = 67). Cardiovascular risk factors, diffusion-weighted imaging patterns of cryptogenic stroke, blood routine, coagulation routine and biochemical routine were compared between the two groups. Multivariable logistic regression and receiver operator characteristic (ROC) curves analysis were used to determine associations between the two groups. Results: Compared with the non-cancer group, the cancer group exhibited higher D-dimer level (P  0.001), fibrin degradation product (FDP, P  0.001), international normalized ratio (INR, P = 0.014), neutrophil to lymphocyte ratio (NLR, P  0.001), platelets to lymphocyte ratio (PLR, P = 0.001), activated partial thromboplastin time (APTT, P = 0.039), more frequent multiple lesions in three circulation (P < 0.001) and lower lymphocytes (P < 0.001), red blood cells (P < 0.001), thrombin time (TT, P = 0.034). Furthermore, D-dimer (AUC = 0.915, P  0.001), FDP (AUC = 0.923, P  0.001), INR (AUC = 0.617, P = 0.014), NLR (AUC = 0.700, P  0.001), PLR (AUC = 0.658, P = 0.001), multiple lesions in three circulation (AUC = 0.786, P < 0.001) had potential diagnostic value in cryptogenic stroke. When combining these 6 parameters, the predictive power was improved (AUC = 0.949, P < 0.001). Conclusions: CST with cancer have unique clinical features, and these potential diagnostic indicators could help patients identify CCS earlier.